An An Analysis of Language Politeness Used in the Interaction in the Classroom at Putra Putri Bangsa Elementary School - Shinta - Anggraini; Ayu Oktaviani; Episiasi Episiasi (Journal of English Education, Literature and Linguistics, 2025)
This research explores the use of language politeness strategies in classroom interactions between an English teacher and fifth-grade students at Putra Putri Bangsa Elementary School. The primary objective of the study is to identify, describe, and analyze the types of politeness strategies used by both the teacher and the students during the English teaching and learning process. A descriptive qualitative research method was used in this study. Data were collected through non-participant observation and documentation techniques, including field notes and video recordings during three classroom sessions conducted in April 2025. The research involved one English teacher and 18 fifth-grade students, comprising nine male and nine female participants. The results revealed a total of 290 politeness strategies used by the teacher, with bald on record being the most dominant (191 occurrences), followed by negative politeness (41), positive politeness (40), and off record (18). Meanwhile, students produced a total of 315 politeness strategies, with positive politeness being the most frequently used (180), followed by off record (45), bald on record (58), and negative politeness (32). These findings show that the teacher commonly employed direct and explicit forms of communication to control the classroom, maintain discipline, and provide clear instructions. Conversely, students more often used polite expressions to show respect, request permission, and maintain harmonious relationships with peers and the teacher. In conclusion, the use of politeness strategies in the classroom setting was appropriate and aligned with each participant’s communicative role. The strategies supported a respectful, effective, and engaging learning environment, emphasizing the importance of politeness in fostering positive teacher-student interactions.